HOGG1 polymorphism and loss of heterozygosity (LOH): significance for lung cancer susceptibility in a caucasian population - Wikman, Harriet; Risch, Angela; Klimek, Fritz; Schmezer, Peter; Spiegelhalder, Bertold; Dienemann, Hendrik; Kayser, Klaus; Schulz, Volker; Drings, Peter; Bartsch, Helmut (International journal of cancer, 2000)
Oxidative damage is implicated in several chronic diseases including cancer. 8‐Hydroxyguanine (8‐oxoG) is one of the major promutagenic DNA lesions, which is produced by reactive oxygen species, caus...
Gesehen am 28.01.2021